Identification and Classification of Thiamine with Amperometric Biosensor Based on Saccharomyces cerevisiae and Principal Component Analysis - Umar, Lazuardi; Rosandi, Vira Annisa; Nainggolan, Leonardus Riski; Setiadi, Rahmondia Nanda; Linda, Tetty Marta (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2023)
Vitamin B1 (thiamine) plays an important role in various metabolic processes and is one of the main factors in the body's health. Thiamine excess and deficiency in the body might cause a variety of diseases such as shortness of breath, beriberi, and heart failure, hence thiamine levels must be detected as a reference for intake. The present research detected thiamine using the amperometric biosensor method and the yeast Saccharomyces cerevisiae as a bioreceptor. Dissolved oxygen (DO) level measurement parameters are considered based on yeast cell metabolism. Thiamine was treated with various concentrations of 15 mM, 30 mM, 45 mM, 60 mM, and 75 mM. The measurement results are in the voltage range of 1912–1964 mV, where the addition of thiamine causes an increase in the reproducibility and growth rate of yeast cells. The ideal characteristics of the biosensor based on the parameters of sensitivity, linearity, and stability was also carried out, which resulted in successive biosensor measurements of 0.925 mV/mM, a correlation coefficient of r = 0.9868, and a decrease in the voltage response of the biosensor up to 4.97% from its initial activity. The measured data were grouped and classified using principal component analysis (PCA), which resulted in a total accumulated data variance percentage of 84.5% and an eigenvalue > 1 for both PCs. It is intended that the findings of this research can be utilized as a reference for controlling vitamin consumption levels that have an impact on health.